Pengaruh Roa, Roe Dan Der Terhadap Pertumbuhan Laba Pada Perusahaan Sub-Sektor Asuransi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - Lailatus Sa’adah; Dwi Widyastuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study was to determine the effect of ROA, ROE, and DER on profit growth in insurance sub-sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The technique used for sampling is purposive sampling method with data from 7 insurance companies. This research is quantitative, which is research presented in the form of numbers and statistics. In determining the accuracy of the model that needs to be done is analyzing financial data, then testing several classical assumptions underlying the regression model. The analysis technique used is multiple linear regression analysis.Data analysis and hypothesis testing in this study using Eviews software version 12.0. The results of this study indicate that ROA has a simultaneous positive effect on earnings growth, while ROE and DER have no significant effect simultaneously on earnings growth. The suggestion in this study is that there is a need to improve the company's financial performance in order to increase company profits so that company prices can increase.